Aktivitas Enzim dan Identifikasi Fenotipik Isolat Kapang Aspergillus Kelompok Flavi Dari DUCC (Diponegoro University Culture Collections) - Karima, Radhita; Rukmi, MG Isworo; Kusumaningrum, Hermin Pancasakti (Bioma : Berkala Ilmiah Biologi, 2020)
Fungi has an important role as decomposer since they can produce hydrolytic enzymes.   The enzyme produced by fungi can be useful for industrial and biotechnology purposes.  Aspergillus section Flavi are known to have the ability in producing several enzymes. The aims of this study were to find out the ability of  Aspergillus  section  Flavi  from  Diponegoro  University  Culture  Collection  in  producing  amylase, protease  and  cellulase  enzymes  and  also  identify  the  species  using  phenotypic  method.  The  fungal enzymatic activity was examined by calculating enzymatic index on specific media. The results showed that all isolates have a potential as enzyme producers.  Phenotypic identification were characterized based on  macro- and micromorphology.  Isolates F130, F80CB, F138 dan F10A were identified as A.tamarii, while F43 and F20A were identified as A.flavus.